Pengaruh Financial Distress Terhadap Tax Avoidance Pada Industri Sektor Konsumsi Tahun 2019-2022. - Baytur Adistiya Oktavia; Gita Arasy Harwida (Indonesian Journal of Applied Accounting and Finance, 2025)
This research aims to provide empirical evidence regarding the influence of financial distress on tax avoidance of industrial companies in the consumption sector in 2019-2022 which are registered with BEI. There are control variables in the research, namely, capital intensity, leverage, sales growth, and firm size. This research is of a quantitative type using multiple linier analysis assisted by SPSS. The data obtained were 47 observations using the purposive sampling method. This research used 2 proxies, namely cash effective tax rate (CETR) and effective tax rate (ETR). The result of this research prove that financial distress has an affect on tax avoidance which is measured using the effective tax rate (ETR). However, the analysis of the control variables shows that using both CETR and ETR the result prove that there are differences between the two proxies. This research provides in-depth insight into factors that influence tax avoidance policies in the consumption sector. The implications of these findings can help companies and decision makers to better understand the internal and external dynamics that influence their future tax planning strategies.